Genetic polymorphism of beta-lactoglobulin and alpha-lactoalbumin in colombian creole cattle by pcr-sscp (2011)
The Colombian Creole Cattle has showed a disturbing decrease in population, from 23,415 individuals in 1999 to 20,102 in 2003.  Despite that many efforts to recover the creole breeds have been done, its future conservation is unclear. Searching for economic desirable genes may contribute to its preservation and utilization as a genetic resource. Genes related with the improvement of milk proteins are considered as an economic important factor by the dairy industry. With the aim of characterizing beta-lactoglobulin (β-LG) and alpha-lactalbumin (α-LA) genes, 30 samples from each of the creole breeds (Blanco Orejinegro, Caqueteño, Casanareño, Costeño Con Cuernos, Chino Santandereano, Hartón del Valle, Romosinuano and Sanmartinero), two Colombian breeds (Lucerna and Velásquez) and two introduced breeds (Holstein and Brahman) were analyzed. A DNA fragment of 262 bp for β-LG and 166 for α-LA using PCR-SSCP were amplified and analyzed. The average frequencies for β-LG (A) and β-LG (B) were 0.46 ± 0.020 and 0.53 ± 0.020, respectively, and 0.35 ± 0.019 for α-LA (A) and 0.64 ± 0.019 for α-LA (B). The genetic diversity (He) average for β-LG was 0.498 and 0.455 for α-LA. Creole breeds represent a valuable genetic base as an alternative for breeding and improvement programs in dairy production herds in order to produce milk with desirable characteristics for the dairy industry.